Impact of E-Learning on Higher Education during Covid-19 Pandemic (LIS TODAY, 2021)
Introduction: In today's scenario learning has stepped into the digital world, in which teaching  professionals and students are virtually connected. E-learning is quite simple to understand and  implement. The use of a desktop, laptop, or smart phones and the internet forms a major component  of this learning methodology. e-learning provides rapid growth and proved to be the best in all  sectors, especially in education during this lockdown. Purpose: This study aims to assess the impact of E-learning on higher education during Covid-19  pandemic among students and teachers. Methods: An online survey was conducted to collect the data. Teachers and students were selected  from different colleges who were conducting online classes during the Covid-19 pandemic. Result: The study found that, a total number of responses are 396 out of which 89.9% students are of  Bachelor’s Degree and 10.1% teachers of Bachelor’s Degree responded to it. Out of 396 responses  249 of the respondents pointed out that online class facility is sufficient to grasp the subject well and  147 of the respondents disagree to it. 74.2% respondents are of the opinion that e-learning is useful  for higher education and 25.8% of respondent are disagree for it.  Conclusion: The study concludes that e-learning can provide a personal learning experience and is  useful for higher education. E-learning helps the users in finding their information easily and there by  improve the quality of learning.
Keywords: E-learning; Covid-19; Higher education